ANALISIS PEMAHAMAN GURU TENTANG DIMENSI DAN TUGAS PERKEMBANGAN PESERTA DIDIK DI SEKOLAH DASAR - Agustin, Cantika Sri; Syifa Rizky Auliya; Dillah Kusmawati; Afaz Maarif Muslim; Wina Mustikaati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers’ understanding of the developmental dimensions and developmental tasks of elementary school students and how this understanding is implemented in the learning process. The problem underlying this study is that learning practices in elementary schools still tend to focus on cognitive achievement, while students’ social, emotional, and moral development has not been optimally integrated into classroom activities. This study employed a qualitative approach with a descriptive method. The research subjects consisted of two elementary school teachers in Purwakarta. Data were collected through observation and semi-structured interviews to obtain in-depth information regarding teachers’ understanding and teaching practices. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that teachers generally have a good understanding of student development as a multidimensional process involving cognitive, social-emotional, and moral aspects. Teachers also recognize differences in students’ characteristics and developmental levels. However, learning practices still predominantly emphasize cognitive aspects, especially basic literacy and numeracy skills. Although teachers have attempted to consider individual differences in teaching, these practices are still intuitive and not fully based on developmental theory. In addition, social and emotional development has not been explicitly integrated into learning activities. Several challenges were identified, including limited time, inadequate facilities, large class sizes, and limited parental support. Therefore, strengthening teachers’ pedagogical competence and collaboration between schools, families, and communities is needed to support holistic student development.